"The Broker of Reality": A Scoping Review of Moral Reconation Therapy. Issue 1 (2nd January 2023) - Harrell, Sam; Johnson, Constance; Boys, Chandler; Suslovic, Brianna; Anderson-Nathe, Ben; Botts, Kassandra
ABSTRACT: Purpose: This scoping review aims to identify the evidence-based literature supporting Moral Reconation Therapy (MRT), a cognitive-behavioral treatment program created in 1987 and implemented in correctional-treatment settings across the US. Social work students and practitioners are among MRT's facilitators. Method: We analyze the reliability and validity of the most recent meta-analysis of MRT, covering studies published between 1988 and 2010. We then identify 669 potential publications on MRT published between 2011 and 2021. Results: Our search across Google Scholar and eleven academic databases yielded zero peer-reviewed studies on MRT's effectiveness or outcomes. Discussion: We explore themes that emerged from the exclusion criteria to describe how MRT's evidence claims are not supported by peer-reviewed research. Social workers should be prepared to assess the reliability, quality, and rigor of evidence supporting the interventions they use. This review offers interesting challenges and learning opportunities for social work students learning about social work research.